A Study of Awareness Challenges on Learning Outcomes - Devaraju, N.B.; Kiran, Raj M; Sujata, B. H. (Educational Trend (A Journal of RIE, Ajmer - NCERT), 2025)
In this study researchers have tried to find out thelevel of awareness and challenges in implementing learning outcomes among teachers, students of 7th standard and their parents. Methodology used by the researchers is mixed method and simple random technique was used to collect the data, techniques used are questionnaire for teachers andheadmasters. Focused group discussion for the students, interview schedule for the parents. The data was analysed using both qualitative and quantitative methods. This study is of consequence because NCERT has come-up with the learning outcome document for the primary level through-out the country and our teachers, students, parents are expected to have awareness on learning outcomes, this research will help us get information regarding the actual level of awareness on learning outcomes among teachers, students, parents and also challenges faced by them.